In the Name of Love: Power Relation and Revictimization on Sexual Violence Case in Courtship (Case Study of Court Decision) - Nike Nadia (Jurnal Perempuan, 2018)
This paper aims to explain the dimensions of inequality power relations and revictimization that occurred in a rape case by seduction in dating violence context. Using the case study of court decisions and radical feminist theory as a tool of analysis, the author argue that the narrative ‘in the name of love’ used by perpetrators of sexual violence in personal relations is actually another manifestation of the inequality of power relations and become site of female body subjugation. Therefore, forms of exploitation that use a ‘proof of love’ narrative in cases of forced sexual intercourse should be identified as part of sexual violence.